PRONUNCIATION IN SPEAKING SKILL STUDENTS OF ENGLISH EDUCATION DEPARTMENT LANCANG KUNING UNIVERSITY - Syaifullah Syaifullah (Universitas Lancang Kuning, 2017)
This research was about students' pronunciation ability in speaking English at University of Lancang Kuning academic year 2015/2016.Type of the research was cross sectional survey design with the aim as an evaluation program. The number of the participant of this research were 36 of third semester of English Education Department Faculty of Education and Teachers Training Lancang Kuning University Pekanbaru which were selected by using simple random sampling.Instrument was used in this research was oral test. In collecting the data, the researcher gave the students test on speaking pronunciation in front of the class. The data gained was analyzed by using descriptive statistic.The researcher found the students' pronunciation in speaking were medium ; some consistent phonemic and foreign stress and intonation patterns but the speaker is intelligible. It was proved by their mean score 1,8. In conclusion to get better pronunciation in speaking skill, the lecturer was suggested to find good strategy in teaching speaking English. Keyword :Pronunciation, Speaking Skill